2014
DOI: 10.48550/arxiv.1405.6089
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Proposal for SPS beam time for the baby MIND and TASD neutrino detector prototypes

R. Asfandiyarov,
R. Bayes,
A. Blondel
et al.

Abstract: The design, construction and testing of neutrino detector prototypes at CERN are ongoing activities. This document reports on the design of solid state baby MIND and TASD detector prototypes and outlines requirements for a test beam at CERN to test these, tentatively planned on the H8 beamline in the North Area, which is equipped with a large aperture magnet. It is hoped that this will allow for the current proposal to be considered in light of the recently approved projects related to neutrino activities with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…The principle for this detector is being optimised at the University of Geneva through the Baby-MIND detector [19] which is conceived as a proof of principle of low energy charge reconstruction using magnetised iron. It has been shown that the detector can be magnetised using aluminium coils which do not reduce the reconstruction efficiency and require minimal power to operate.…”
Section: Magnetised Muon Range Detectormentioning
confidence: 99%
See 2 more Smart Citations
“…The principle for this detector is being optimised at the University of Geneva through the Baby-MIND detector [19] which is conceived as a proof of principle of low energy charge reconstruction using magnetised iron. It has been shown that the detector can be magnetised using aluminium coils which do not reduce the reconstruction efficiency and require minimal power to operate.…”
Section: Magnetised Muon Range Detectormentioning
confidence: 99%
“…It has been shown that the detector can be magnetised using aluminium coils which do not reduce the reconstruction efficiency and require minimal power to operate. This design is discussed in detail in [19]. It has been accepted as part of the WAGASCI experiment [20].…”
Section: Magnetised Muon Range Detectormentioning
confidence: 99%
See 1 more Smart Citation
“…A proof-of-principal detector is being constructed by the University of Geneva [11] for use in the WAGASCI experiment [12] at J-PARC. This data will then be used to optimise the MRD design for TITUS.…”
Section: Magnetised Muon Range Detectorsmentioning
confidence: 99%